Comparison of eye measurements between young Korean women with inborn double eyelids and those with single eyelids - Jung, Han Byul; Han, Dong Gil; Shim, Jeong Su; Lee, Yong Jig; Kim, Sung-Eun (Archives of Aesthetic Plastic Surgery, 2020)
Background Eye measurements in Koreans have been studied extensively, but researchers have reported widely differing values, even for the same parameters. These discrepancies are likely due to inconsistencies in the proportions of subjects with double eyelids included in their studies. We retrospectively studied eye measurements according to the presence or absence of double eyelids, and compared the results to those of previous studies. Methods We conducted anthropometric measurements of eyes in young (20–29 years) Korean women with no congenital malformation, trauma, or surgery of the eyelids. The participants were dichotomized according to the presence of double eyelids, resulting in 116 eyes with single eyelids and 124 with double eyelids. We measured the palpebral fissure length (PFL), palpebral fissure height (PFH), margin reflex distance 1 (MRD1), intercanthal distance (ICD), interpupillary distance (IPD), outer canthal distance (OCD), and inclination of the palpebral fissure in each eye. Results The mean PFL was 24.1 mm in the single-eyelid group and 25.5 mm in the double-eyelid group. The other mean values for the two groups were as follows: PFH, 8.0 mm and 9.9 mm, respectively; MRD1, 2.8 mm and 4.1 mm, respectively; IPD, 61.6 mm and 62.8 mm, respectively; and OCD, 85.3 mm and 87.9 mm, respectively. Conclusions In the double-eyelid group, the horizontal and vertical length of the eye was greater than in the single-eyelid group, and the mean values of IPD, OCD, PFL, PFH, and MRD1 were statistically significantly higher.